Peran Media Sosial dalam Membentuk Preferensi Musik Generasi Z di Indonesia - Apriliyanti, Tanti Riski (Universitas Pendidikan Ganesha, 2025)
Social media has become an integral part of Generation Z's daily life, especially in Indonesia. This journal aims to analyze how social media influences this generation's music preferences. Using a qualitative approach, this study explores the role of platforms such as Instagram, TikTok and YouTube in introducing and promoting certain music genres, artists and songs. The results show that social media algorithms, viral content and digital social interactions are the main factors shaping Generation Z's music preferences. These findings highlight the importance of social media as an effective music promotion tool as well as a platform to express the younger generation's musical identity